Colonial Racial Ethnocentrism Towards Indigenous People in a Short Story Collection “Semua untuk Hindia” by Iksaka Banu (A Postcolonial Study) - Nensilianti Nensilianti; Sy. Fatma Al-Khiyyed; Hasvivi Tri Anjarsari Fahrir (IAIN MADURA, 2021)
Dutch colonialism in Indonesia brought about physical oppression and conquest of territory and instilled racism. Understanding racism positions the indigenous people as a third class whose rank has never been higher than the Dutch. Racial ethnocentrism leads people to concepts and views of life that consider their culture to be far superior to the culture owned by others. This study aimed to reveal and describe the forms of racial ethnocentrism brought by the Dutch towards Indonesian society. The data were obtained from excerpts or quotes that contain elements of racism from a short story collection “Semua untuk Hindia (All for Hindia)” by Iksaka Banu. The analysis results revealed that racial ethnocentrism or racism emerged in racial prejudice, stereotypes, and discrimination in the short story collection. The cultivation of these ethnocentric behaviors was based on the Western cultural concept and view of ideal human beings and the human position passed down from generation to generation. It impacted the Dutch’s social construction and use of authority in oppressing the indigenous people in Indonesia. Indigenous figures were oppressed, marginalized, and their human rights were ignored. Research on the short story collection can strengthen the disclosure of colonialism history in Indonesia.